Determining Influencer Compensation Based on Engagement Metrics in Customer Recovery Campaigns - Irfandi, Irfandi (Journal of Social Commerce, 2023)
This have a look at focuses on influencer reimbursement and Likes, Comments, Shares, and Views attached to purchaser recuperation campaigns. Addressing the research problem, the study adopts a quantitative research strategy, and it collects descriptive and inferential data and explores the correlations and relationships between the variables with the help of correlation, regression, analysis of variance  and analysis of covariance  that affect compensation. It also observes that a higher level of engagement such as Likes, and Views is highly associated with longer reimbursement. The look at addresses some of the voids in current literature by employing imparting a detailed account on character and combination consequences of engagement metrics on compensation. The investigation of this examine supplies invaluable findings to fashion additional efficient compensation methods in influencer promoting, the requirement for a various approach to evaluate influencer effectiveness.